Mapping of the available standards against the regulatory needs for nanomedicines. (20th June 2018) - Halamoda‐Kenzaoui, Blanka; Holzwarth, Uwe; Roebben, Gert; Bogni, Alessia; Bremer‐Hoffmann, Susanne
Abstract : Appropriate documentary standards and reference materials are crucial building blocks for the development of innovative products. In order to support the emerging sector of nanomedicine, relevant standards must be identified and/or developed before the products will enter into the regulatory approval process. The anticipation of standardization needs requires a good understanding on the regulatory information requirements that can be triggered by the particularities of nanomedicines. However, robust datasets allowing firm conclusions on regulatory demands are not yet available due to a lack of regulatory experience with innovative products. Such a catch‐22 situation can only be advanced in an iterative process by monitoring continuously the scientific evidence and by promoting intensive knowledge exchange between all involved stakeholders. In this study, we have compiled information requirements released by regulatory scientists so far and mapped it against available standards that could be of relevance for nanomedicines. Our gap analysis clearly demonstrated that for some endpoints such as drug release/loading and the interaction of nanomedicines with the immune system no standards are available so far. The emerging nanomedicine sector could benefit from cross‐sector collaboration and review the suitability of standards that have been developed for nanomaterials used for other industrial applications. Only a concerted action of all parties can lead to a smooth translation of nanomedicines to clinical application and to the market. This is in particular important because nanotechnology‐based drug delivery systems are key for the development and implementation of personalized medicine. This article is characterized under: Toxicology and Regulatory Issues in Nanomedicine > Regulatory and Policy Issues in Nanomedicine Abstract : Identification of regulatory needs for nanomedicines includes clarification of information requirements and evaluation of the availability of the relevant standards.